An experimental study on the detection mechanism of 2-CEES using SAW sensors under various temperature conditions - Hee-Chan Jang; Sanjeeb Lama; Jaeyoung Heo; Changsik Song; Young-Jun Lee; Jun-Soo Lee; Joo-Hyung Kim (Scientific Reports)
Abstract Among chemical warfare agents (CWAs), mustard gas (HD) is a lethal blister agent that causes prolonged chemical burns and skin blistering, often without immediate symptoms. HD has been used as a chemical weapon due to its potent toxicity, which becomes more pronounced as temperatures rise after its release in colder conditions. As temperature increases, HD also undergoes more active desorption, making its detection increasingly difficult. Therefore, temperature-sensitive detection methods are critical for effectively identifying HD for practical applications in this field. In this study, we investigated the detection of 2-chloroethyl ethyl sulfide (2-CEES), a simulant for HD, using a surface acoustic wave (SAW) sensor coated with a polyphosphonamide-based polymer (PPD-F2). Experiments were conducted across a temperature range of − 20 °C to 50 °C. The results demonstrated that the sensor’s frequency shift (∆f) increased as the temperature decreased, with a particularly notable rise in ∆f observed at temperatures below 10 °C.